Fasudil on Myocardial Injury in Rats with Myocardial Ischemia and Reperfusion through Rho-ROCK Signal Pathway - Zhu, Zhiyun; Qiu, Bo; Wang, Qiang; Wei, Wei; Huang, Jinlong; Duan, Wenfen (Cellular and Molecular Biology, 2022)
Cardiovascular diseases are very harmful to human life and health. Reperfusion therapy is a standard method to treat cardiovascular diseases and has achieved high clinical effects. However, this treatment method is likely to cause myocardial ischemia-reperfusion injury. It has been reported that the Rho kinase inhibitor fasudil can interfere with cardiomyocyte apoptosis through the Rho-ROCK signaling pathway, so it is often used to treat cardiovascular diseases. The essay aims to research this specific influence of fasudil on cardiac damage in myocardial ischemia-reperfusion mouses through the Rho-ROCK signal path and its related mechanisms. Forty rats were taken as the research object, and the mouses were separated into control clusters. In the observation cluster of fasudil, the rat heart device was perfused by surgery. The rat coronary artery was ligated for 20 minutes to make the rat myocardial ischemia. Then, the ligation was loosened for myocardial perfusion to create a rat myocardial ischemia-reperfusion model. Observation group rats were perfused with quantitative fasudil, 80 minutes after ischemia-reperfusion, the ultrastructural changes and myocardial ischemic area of the rat myocardium were observed under a microscope, and the dynamic changes of the mouse heart were examined by flow cytometry. The PCR fluorescence method was used to explore the outlook layer of Rho-ROCK kinase activity to detect rat cardiomyocyte apoptosis. It is shown that under this intervention of fasudil, this expression level of Rho-ROCK kinase activity in the observation group was reduced by 18.3%, the myocardial cell apoptosis rate was decreased by 26.4%, and one area of myocardial ischemia can be reduced by 32.5%. The ultrastructure of the new object in rats is improved, and the left ventricular diastolic and systolic effect is enhanced. Therefore, the fasudil may decrease cardiac ischemia and focus on injured Rho-ROCK signal path activity.